Exploring WhatsApp groups as a digital collection sharing platform for libraries - Irfana, Maisyatus Su'adaa; Susanti, Dian Arya; Anna, Nove Eka Variant; Rounds, Gwen (Universitas Padjadjaran, 2026)
Background: WhatsApp Groups (WAGs) are widely used as communication and collaboration tools among librarians. However, their role in digital collection sharing and informal interlibrary loan has received little attention, particularly in developing-country contexts. Understanding how WAGs can support library resource sharing addresses this research gap. Purpose: This study aims to explore how librarians use WAGs as a platform for digital collection sharing to fulfil users' information needs and to examine their potential as an informal extension of the interlibrary loan system. Methods: Non-participant observation was conducted in several WhatsApp groups of librarians in Indonesia. The study focused on how group members requested and shared digital resources, such as journal articles and ebooks, during their daily professional communication. Results: Findings indicated that some librarians actively used WAGs to exchange digital collections. Members posted requests for specific articles or ebooks, and others responded by sharing full-text files when available. This practice fostered collaboration and helped overcome subscription and budget constraints. However, challenges such as copyright compliance, file-size constraints, limited information organization, and data privacy and security issues were also identified. Conclusion: WAGs can informally replicate the functions of formal resource-sharing systems, offering flexible, low-cost opportunities for collaboration. Effective implementation requires clear regulations, membership controls, attention to privacy and security, and appropriate training. Implications: In practice, WAGs offer a lightweight, cost-effective model for library collaboration. Theoretically, this study contributes empirical evidence on informal digital collection sharing, informing policies and governance strategies for library digital resources and AI-adjacent platform-mediated knowledge exchange.